Sinkronisasi Kebijakan dan Capaian Kinerja: Mana yang Didahulukan? - Umi Listyaningsih; Sukamdi; Sonyaruri Satiti Ruri; Reni Pebrianti (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
Synchronization of development policies in the field of population and family planning is an issue in the central, provincial and district/city governments as stipulated in Law No. 23/2014. Article 8 paragraph 2 of the Law states that population quantity control is carried out through synchronization of population policies at the national level and regions. Therefore, work programs in the population control at the district/city level are highly varied according to the problem. Family planning promotion, counseling and advocacy are programs in all districts/cities targeting the couples of childbearing age and adolescents. The study of program plan and regulatory documents for the 2019-2024 fiscal year became the basis for focused discussions with various levels of government, namely the central, provincial, regency/city and sub-district level. Targets, strategies, programs and activities which include types, objectives, objectives, coverage and achievements are components to be examined for content, consistency and synchronization. Meanwhile, policy synchronization can be seen from the formulation of work programs. The results of the study show that directly, the provincial work program is linear with the national agenda.